Yorùbá Theatre Practice and Nollywood - Shola Balogun (Media and Intercultural Communication: A Multidisciplinary Journal)
The development of theatre in Yorùbáland evolving from travelling actors to the contemporaneous practice of the culture in the film medium is an intriguing phase of maturity of the Yorùbá people’s theatrical tradition. Nollywood has made the whole world a stage for Yorùbá theatre. By extending the performance space beyond the physical confines of the auditorium, Nollywood represents both the current state and future direction of Yorùbá theatre. The demand for relevance and the focus on contemporary audience interests all play a significant part in the shift of Yorùbá theatre from stage to film medium. Nollywood has helped Yorùbá theatre practice by preserving Yorùbá stories, enhancing widespread acceptance and attracting global attention. Yorùbá theatre serves as an exposition of Yorùbá tradition and culture; thus, understanding the worldviews of its creators is essential for appreciating its current practice and the factors influencing its representation in Nollywood. This paper aims to highlight the importance of understanding the theatre developed in Yorùbáland and how its culture is depicted in the film adaptation of Akínwùmí Ìṣọ̀lá's Ṣaworoidẹ (Brass Bells).